2013
DOI: 10.14314/polimery.2013.557
|View full text |Cite
|
Sign up to set email alerts
|

Polypropylene nonwovens with natural polymers addition for filtration applications

Abstract: Polypropylene nonwovens with natural polymers addition for filtration applicationsSummary -Polypropylene composite nonwovens with microcrystalline cellulose (2 wt. %) and microbiological chitosan (3 wt. %) addition were processed by the melt-blown technique. The nonwovens were studied for filtration parameters and bio-destruction degree and the effect of chitosan on antibacterial properties of the polypropylene nonwoven was analyzed. The addition of modifiers resulted in impairing filtration parameters of poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
0
5
0
2
Order By: Relevance
“…Melt-Blown Technique PLA nonwovens were made by the melt-blown technique using a single-screw laboratory extruder (Axon, Sweden) with a head with 30 holes of 0.35 mm diameter each, compressed air heater As part of our research program on the functionalization of biomolecules [44][45][46][47][48][49], biopolymers and polymers [50][51][52][53][54], we present the preparation and biological exploration of a polymer hybrid based on polylactic (PLA) nonwoven fabric with surface modified by potassium iodide.…”
Section: Poly(lactide) Nonwoven Fabricsmentioning
confidence: 99%
See 1 more Smart Citation
“…Melt-Blown Technique PLA nonwovens were made by the melt-blown technique using a single-screw laboratory extruder (Axon, Sweden) with a head with 30 holes of 0.35 mm diameter each, compressed air heater As part of our research program on the functionalization of biomolecules [44][45][46][47][48][49], biopolymers and polymers [50][51][52][53][54], we present the preparation and biological exploration of a polymer hybrid based on polylactic (PLA) nonwoven fabric with surface modified by potassium iodide.…”
Section: Poly(lactide) Nonwoven Fabricsmentioning
confidence: 99%
“…As part of our research program on the functionalization of biomolecules [44][45][46][47][48][49], biopolymers and polymers [50][51][52][53][54], we present the preparation and biological exploration of a polymer hybrid based on polylactic (PLA) nonwoven fabric with surface modified by potassium iodide.…”
Section: Introductionmentioning
confidence: 99%
“…There is a broad range of different polymers which may be used in the melt-blowing process such as polystyrene, polyesters, polyamides, polyethylene, polycarbonate, polyurethane, polyphenylene sulfide but the one used most commonly is polypropylene [31]. Nowadays most nonwovens are made of neat polymers but there are some works that describes melt-blowing process in the presence of polyethylene glycol, magnesium stearate or silver nanoparticles to strengthen the filtration properties of the nonwovens [32,33] or with microcrystalline cellulose and microbiological chitosan to make them biodegradable [34]. For improvement of their thermomechanical properties, the nonwovens were fabricated with an addition of organo-modified nanoclay [35] or with graphite [36] as well as with CNT to obtain the temperature-sensitive sensors [37].…”
Section: Introductionmentioning
confidence: 99%
“…
Recently, a substantial body of research has shown interesting possibilities of using nonwoven structures in advanced applications in a variety of sectors, including the construction industry, medicine, transportation, textiles, the automotive industry, and so on [4][5][6]. Such nonwovens may differ in terms of quantitative and qualitative composition, morphological structure, physical and chemical properties of the incorporated modifiers, hydrophilicity and hydrophobicity, as well as structural modification technologies [7][8][9][10][11][12][13][14][15][16].Over the past years, increased sensitivity to micro-and nanometric particles has induced greater user expectations concerning enhanced filtering properties of nonwovens. Highquality PP melt-blown nonwovens are needed, for instance, in sectors using the so-called clean technologies [17,18].
…”
mentioning
confidence: 99%
“…Recently, a substantial body of research has shown interesting possibilities of using nonwoven structures in advanced applications in a variety of sectors, including the construction industry, medicine, transportation, textiles, the automotive industry, and so on [4][5][6]. Such nonwovens may differ in terms of quantitative and qualitative composition, morphological structure, physical and chemical properties of the incorporated modifiers, hydrophilicity and hydrophobicity, as well as structural modification technologies [7][8][9][10][11][12][13][14][15][16].…”
mentioning
confidence: 99%